2013
DOI: 10.1080/10942912.2011.567430
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seed Size and Microstructure on Their Mechanical Properties and Frictional Behavior

Abstract: The seeds of grass pea were selected based on their size, hardness, and microstructure in order to examine their mechanical properties and friction coefficients versus mass. The size, shape, mass, and static friction coefficients of seeds were determined using adequate methods. Seed hardness was measured using compression methods, and it was described by typical and corrected fracture parameters. The microstructure of cotyledons and seed surfaces was viewed using scanning electron microscopy, and surface micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…A similar trend was reported for cut plantain fingers, where the energy required to rupture a cut-out section of the finger increased from 0.259 J to 0.410 J as the cut size section increased from 5.45 cm 3 to 9.45 cm 3 [15]. According to Sadowska [19], despite variability of the size and the fracture force of seeds representing different accessions and varieties, there was a clear tendency towards an increase in fracture force along with an increase in seed size. Like the bio-yield parameters, all the rupture parameters (force, energy and relative deformation) increased with increase in the finger's size, but higher in the local variety.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…A similar trend was reported for cut plantain fingers, where the energy required to rupture a cut-out section of the finger increased from 0.259 J to 0.410 J as the cut size section increased from 5.45 cm 3 to 9.45 cm 3 [15]. According to Sadowska [19], despite variability of the size and the fracture force of seeds representing different accessions and varieties, there was a clear tendency towards an increase in fracture force along with an increase in seed size. Like the bio-yield parameters, all the rupture parameters (force, energy and relative deformation) increased with increase in the finger's size, but higher in the local variety.…”
Section: Resultssupporting
confidence: 72%
“…The surface of contact between the sample and the compression plate changes during compression, making compression stress, the most popular and univocal physical parameter, difficult to use [19]. Fifteen replications were used for the experiment.…”
Section: Mechanical Properties Determinationmentioning
confidence: 99%
“…Also during processing operation like oil extraction, SAMNUT 11 kernels will require lesser compressive energy and lower power consumption than the SAMNUT 10 kernels. According to Sadowska [19], despite variability of the size and the fracture force of seeds representing different accessions and varieties, there was a clear tendency towards an increase in fracture force along with an increase in seed size. These results were similar to those reported by Aydin C and Ozcan M [20] for terebinth and [21] for almond kernel.…”
Section: Resultsmentioning
confidence: 99%
“…The disparities in the rupture force values recorded by different authors could be attributed to soil condition, agricultural practices, environmental conditions, harvesting time, and groundnut variety. Sadowska et al (2013) observed a clear increment in the fracture force of grass pea (Lathyrus sativus L.) seed, as the seed size increases; despite its variability, accessions and varieties (Sadowska et al, 2013). Deformation at rupture point Figure 5 showed the deformation level of a groundnut kernel at rupture point.…”
Section: Resultsmentioning
confidence: 99%